CSR in the Digital Era: How Technology Is Transforming Corporate Social Responsibility - Lila Alwyah; Ernaldo Fikrul Arifin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The rapid advancement of digital technology in the Industry 4.0 era has brought fundamental changes to the implementation of Corporate Social Responsibility (CSR) in the business sector. This study aims to identify the forms of digital technology utilization in CSR programs, analyze its impact on program effectiveness, and formulate a conceptual framework for digital CSR relevant to the Indonesian context. The research employs a systematic literature review (SLR) using the PRISMA framework, supported by an analysis of CSR reports from 15 selected companies in Indonesia covering the period 2019–2023. The findings reveal that CSR digitalization operates through four main clusters: (1) stakeholder communication and engagement via social media and digital platforms; (2) data-driven decision-making powered by big data and artificial intelligence; (3) enhanced transparency and accountability through blockchain technology; and (4) more participatory community empowerment via digital applications. Case studies from companies such as PT Telkom Indonesia, PT PLN, and BRI demonstrate that the adoption of digital technology in CSR can improve budget efficiency, expand program reach, and produce more measurable social impact. However, significant challenges remain, including the digital divide, the risk of digital greenwashing, data privacy concerns, and limited human resource capacity. This study proposes a four-dimensional Digital CSR framework: digital infrastructure, governance and regulation, capacity and ecosystem, and impact and accountability as a guide for Indonesian companies in effectively, inclusively, and sustainably integrating technology into their CSR strategies.